Mapping and Visualizing the Social Work Curriculum. Issue 2 (3rd July 2019) - Ballantyne, Neil; Hay, Kathryn; Beddoe, Liz; Maidment, Jane; Walker, Shayne
Abstract: This is a methodological article describing how a national social work education research project constructed a taxonomy of educational terms and used database and data visualization software to map the social work curriculum in New Zealand. Mapping the curriculum is difficult enough in the context of a single educational program, however, representing and exploring curriculum topics across the 14 different educational institutions participating in this study presented formidable difficulties. This article explores the approach to curriculum mapping used by the research team and discusses the technologies and information science principles used to classify, map, and visualize curriculum content. It will explain how the researchers constructed a taxonomy of over 600 educational terms, describe how the taxonomy was used to index 402 curriculum documents in a relational database, and illustrate the creation of curriculum visualizations using the Tableau™ data visualization software. The way in which findings from this part of the study will inform subsequent phases of the research will be discussed. The strengths and limitations of the methodology will be noted and opportunities to use the assets created by the project for future endeavors identified.